2016
DOI: 10.1007/s00436-016-5267-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat-stressed Metarhizium anisopliae: viability (in vitro) and virulence (in vivo) assessments against the tick Rhipicephalus sanguineus

Abstract: The current study investigated the thermotolerance of Metarhizium anisopliae s.l. conidia from the commercial products Metarril® SP Organic and Metarril® WP. The efficacy of these M. anisopliae formulations against the tick Rhipicephalus sanguineus s.l. was studied in laboratory under optimum or heat-stress conditions. The products were prepared in water [Tween® 80, 0.01 % (v/v)] or pure mineral oil. Conidia from Metarril® SP Organic suspended in water presented markedly delayed germination after heating to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…In the present study, we examined the deleterious effects of water temperature and exposure time in water on formulated and unformulated conidia of B. bassiana and M. anisopliae and then on the ability of treated conidia to infect an insect host. Although the negative effect of high temperatures on formulated conidia has been previously described only in shelf-life studies (Alves et al, 2002;Hedgecock et al, 1995;McClatchie et al, 1994;Starthers et al, 1993) and for conidia diluted in mineral oil (Barreto et al, 2016;Alves et al, 2016), we are the first to report on the partial protection provided by emulsifiable oil to conidia against high temperatures in oil-in-water suspensions, with reductions in conidia death and with conidia maintaining infectivity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the present study, we examined the deleterious effects of water temperature and exposure time in water on formulated and unformulated conidia of B. bassiana and M. anisopliae and then on the ability of treated conidia to infect an insect host. Although the negative effect of high temperatures on formulated conidia has been previously described only in shelf-life studies (Alves et al, 2002;Hedgecock et al, 1995;McClatchie et al, 1994;Starthers et al, 1993) and for conidia diluted in mineral oil (Barreto et al, 2016;Alves et al, 2016), we are the first to report on the partial protection provided by emulsifiable oil to conidia against high temperatures in oil-in-water suspensions, with reductions in conidia death and with conidia maintaining infectivity.…”
Section: Discussionmentioning
confidence: 55%
“…The negative effect of temperature on conidia viability has received particular attention. However, the effect of temperature on conidia formulations has been evaluated primarily in shelf-life studies (Alves et al, 2002;Hedgecock et al, 1995;Moore et al, 1995;Starthers et al, 1993;McClatchie et al, 1994) or with conidia diluted in mineral oil (Barreto et al, 2016;Alves et al, 2016), and little is known about the harmful effects of water temperature and exposure time in tank mixtures immediately before use.…”
Section: Introductionmentioning
confidence: 99%
“…Here, M. robertsii ARSEF 2575 was virulent to R. microplus engorged females after fungal inoculation. Several factors are involved in the virulence of a fungal isolate to arthropods, especially ticks that are much less susceptible than insects (Rot et al, 2013; Erler and Ates, 2015; Mohammadyani et al, 2016; Alves et al, 2017; Fischhoff et al, 2017). Distinct fungal virulence to different populations of the same host (Perinotto et al, 2012), host species, life stage of the host (i.e., some species and stages are more susceptible than others), and the quantity of fungal propagules applied to the arthropod pest (Alden et al, 2001; Ment et al, 2012) are some of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of oil formulation, oil-in-water emulsion formulation, and water formulation of M. anisopliae conidia has been tested and compared for different hosts. Oil formulated conidia caused higher mortality in hosts compared to water formulated conidia [ 3 , 8 , 25 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Besides, oil formulated conidia were found to provide thermotolerant protection to the conidia and remain effective even under low humidity conditions.…”
Section: Conidia Formulation For Metarhizium Anisopliae mentioning
confidence: 99%
“…The efficacy of M. anisopliae in killing the nymphs and adults of many genus and species of ticks has been demonstrated in many studies for Rhipicephalus microplus , Rhipicephalus sanguineus , Haemaphysalis qinghaiensis , Hyalomma excavatum , and Ixodes ricinus [ 25 , 28 , 76 , 78 , 101 , 102 , 103 , 104 , 105 ]. Although studies have shown that the conidia of M. anisopliae reduced the percentage of egg production and hatchability, the precise mechanism of how M. anisopliae caused a decline in egg production and hatchability is still unknown [ 105 , 106 ].…”
Section: Metarhizium Anisopliae As a Biologicalmentioning
confidence: 99%